2021
DOI: 10.3390/s21113589
|View full text |Cite
|
Sign up to set email alerts
|

Bluetooth 5.1: An Analysis of Direction Finding Capability for High-Precision Location Services

Abstract: This paper presents an in-depth overview of the Bluetooth 5.1 Direction Finding standard’s potentials, thanks to enhancing the Bluetooth Low Energy (BLE) firmware. This improvement allows producers to create location applications based on the Angle of Departure (AoD) and the Angle of Arrival (AoA). Accordingly, it is conceivable to design proper Indoor Positioning Systems (IPS), for instance, for the traceability of resources, assets, and people. First of all, Radio Frequency (RF) radiogoniometry techniques, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(29 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…• Gaming consoles • Industrial Bluetooth Mesh Networking [41] • BL based direction finding for cm level positional accuracy [42], [43] • Advertising services [44], [45] Bluetooth Low Energy (BLE) is a variant of BL that uses 40 channel (2 MHz) as compared to 79 channels (1 MHz) of the classic BL. BLE is designed for prolonged low power operation and also supports for supports mesh networking.…”
Section: Bluetoothmentioning
confidence: 99%
“…• Gaming consoles • Industrial Bluetooth Mesh Networking [41] • BL based direction finding for cm level positional accuracy [42], [43] • Advertising services [44], [45] Bluetooth Low Energy (BLE) is a variant of BL that uses 40 channel (2 MHz) as compared to 79 channels (1 MHz) of the classic BL. BLE is designed for prolonged low power operation and also supports for supports mesh networking.…”
Section: Bluetoothmentioning
confidence: 99%
“…This extension does not carry any data [6], but allows the receiver to consecutively sample the symbols by switching between multiple antennas to determine the AoA information from the RF phase differences, thus mimicking multiple-input and multiple-output (MIMO) technology (Fig. 2) [7]. Although being close to the strictly simultaneous JCAP with indoor sub-meter accuracy, there is still RF energy and channel occupancy intended for either communication or positioning, but not both simultaneously.…”
Section: A Ubiquitous Localization and Sensingmentioning
confidence: 99%
“…The system itself is well optimized for accurate, fast and robust SSL performance, but in the first iteration of our deployment, we found that using sound was susceptible to interference and the transmission distance was too short. Fortunately, the new Bluetooth 5.1 Direction Finding standard can provide us with higher precision, a much longer range, and more robust source localization and tracking performance [30], making auditory feasible for swarm robots.…”
Section: Auditory (Bluetooth Aoamentioning
confidence: 99%
“…Although the Bluetooth signal is used to mimic the audible sound, no state data is shared. Our implementation takes advantage of the new Bluetooth 5.1 Direction Finding standard that can provide us with sub-meter precision, a much longer range (roughly 30-50 meters range with 4-0 walls blocking respectively tested by us), and more robust source localization and tracking performance than real sound [30].…”
Section: A Hardware Setup and Testingmentioning
confidence: 99%